Effect of a partnership care programme on quality of life in school-age children with leukaemia: a controlled clinical trial. (2nd February 2023) - Mofidi, Afsaneh; Khan Kermanshahi, Sima Mohammad; Jaseb, Kaveh
Abstract : Background: Despite the low quality of life (QoL) of children with leukaemia, there is a lack of well-designed and culture-oriented care programmes to improve it. The Partnership Care Model (PCM), which was developed based on the Iranian culture, seems to be effective in improving the QoL in children living with chronic diseases. Aim: This study aimed to evaluate the effect of a care programme based on the PCM on the QoL of children with leukaemia. Methods: This controlled clinical trial encompassed 60 school-age children with leukaemia and their mothers. In the experimental group (n=30), a 2-month care programme was implemented based on the PCM, including the four stages of motivation, preparation, involvement and evaluation. Only standard care was provided to the control group (n=30). Children's QoL was assessed using the Paediatric Quality of Life Inventory 3.0 Cancer Module in the pre-test phase and 2 months after the intervention. Findings: The total score of QoL and all its subscales were significantly higher in the experimental group than the control group in the post-test phase (p<0.001). Moreover, a significant difference was observed between pre-test and post-test scores in all domains in the experimental group (p<0.001); however, no significant difference was noticed between the scores in the control group. Conclusion: The partnership care programme seems to improve the QoL in children with leukaemia. Future investigations are recommended to shed further light on the findings of this study.